Intrapericardial injection of hydrogels with ASC and their secretome to treat dilated cardiomyopathies - Tácia Tavares Aquinas Liguori; Gabriel Romero Liguori; Viktor Sinkunas; Cristiano Jesus Correia; Raphael dos Santos Coutinho e Silva; Fernando Luiz Zanoni; Vera Demarchi Aiello; Martin Conrad Harmsen; Luiz Felipe Pinho Moreira (Scientific Reports)
Abstract Doxorubicin-induced cardiomyopathy (DOX-IC) is a significant and common complication in patients undergoing chemotherapy, leading to cardiac remodeling and reduced heart function. We hypothesized that the intrapericardial injection of hydrogels derived from the cardiac decellularized extracellular matrix (dECM) loaded with adipose tissue-derived stromal cells (ASC) and their secretome dampens or reverses the progression of DOX-IC. DOX-IC was induced in Wistar male rats through ten weekly intra-peritoneal injections of doxorubicin (cumulative dose: 18 mg/kg). We performed intrapericardial treatment in week five with dECM hydrogel loaded with ASC and their conditioned medium (CMed). The volume of intrapericardial injection was 2 ml/kg, the ASC density was 20 million/mL, while the hydrogel contained 100-fold concentrated CMed. Interstitial myocardial fibrosis was assessed by PicroSirius Red staining and hemodynamics parameters in pressure-volume loops. Compared to saline controls, interstitial myocardial fibrosis was reduced in ASC/CMed-loaded hydrogels treated animals (p = 0.0139). Ejection fraction and cardiac work efficiency improved in the ASC/CMed-treated rats compared to saline treatment (p = 0.0151 and p = 0.0655, respectively). The intrapericardial injection of dECM hydrogels loaded with ASC and their secretome warrants a novel therapeutic modality to improve ventricular hemodynamics and reduce cardiac remodeling in DOX-IC.